Pengaruh Trust Terhadap Intention To Purchase pada Pembelian Clothing Fashion Zara Oleh Konsumen Kota Surabaya - Adelia Intan Diah Ayu Pitaloka (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Trust plays an important role in building customer loyalty. Consumers who have built trust towards a brand or company tend to become loyal customers and repurchase consumer products or services. Consumers will also feel more comfortable paying higher prices for products or services that have a higher level of trust. ZARA fashion clothing original products are preferred by consumers in urabaya compared to KW or imitation products. In this case, consumers have become aware of the integrity aspect that arises from the consumer's attitude, where they understand that buying genuine products is more advisable considering the price compared to the existing quality.